The Dietary Biomarkers Development Consortium: An Initiative for Discovery and Validation of Dietary Biomarkers for Precision Nutrition - Hrishikesh Chakraborty; Qi Sun; Shilpa N Bhupathiraju; Jeannette M Schenk; Darya O Mishchuk; James R Bain; Xuan He; Jianghao Sun; James Harnly; William Simmons; Daniel Raftery; Liming Liang; et al. (Current Developments in Nutrition)
Diet is a complex exposure that affects health across the lifespan. Objective biomarkers that can reliably reflect intake of nutrients, foods, and dietary patterns with sufficient accuracy are an important tool for assessing associations of diet with health outcomes. Advances in metabolomics, coupled with feeding trials and high-dimensional bioinformatics analyses, pave the way for discovering compounds that can serve as sensitive and specific biomarkers of dietary exposures. The Dietary Biomarkers Development Consortium (DBDC) is leading the first major effort to improve dietary assessment through the discovery and validation of biomarkers for foods commonly consumed in the United States diet. To achieve this goal, a 3-phase approach will be implemented to identify, evaluate, and validate food biomarkers. In phase 1, 3 controlled feeding trial designs will be implemented by administering test foods in prespecified amounts to healthy participants, followed by metabolomic profiling of blood and urine specimens collected during the feeding trials to identify candidate compounds. Data from these studies will characterize the pharmacokinetic parameters of candidate biomarkers associated with specific foods. In phase 2, the ability of candidate biomarkers to identify individuals eating the biomarker-associated foods will be evaluated using controlled feeding studies of various dietary patterns. In phase 3, the validity of candidate biomarkers to predict recent and habitual consumption of specific test foods will be evaluated in independent observational settings. Data generated during all study phases will be archived in a publicly accessible database as a resource for the research community. The DBDC aims to significantly expand the list of validated biomarkers of intake for foods consumed in the United States diet, which can help advance understanding of how diet influences human health. This manuscript discusses the DBDC’s organizational infrastructure, study design, laboratory methods, and strategies for dietary biomarker discovery and validation. Trial registration number: This trial was registered at Phase 1 Seattle Dietary Biomarkers Development Center (P1-SDBDC) as NCT05580653, at Fruit and Vegetable Biomarker Discovery (UCD-DBDC) as NCT05621863, and at Dietary Biomarkers Intervention Core as NCT05616585.